Pathogenic Vibrio parahaemolyticus indiarrhoeal patients, fish and aquatic environments and their potential for inter-source transmission. Issue 5 (May 2019) - Guin, Sailen; Saravanan, Murugan; Anjay,; Chowdhury, Goutam; Pazhani, Gururaja Perumal; Ramamurthy, Thandavarayan; Chandra Das, Suresh
Abstract: The role of Vibrio parahaemolyticus in causing diarrhoeal disease is well known. However, phenotypic and genetic traits of this pathogen isolated from diverse sources have not been investigated in detail. In this study, we have screened samples from diarrhoeal cases (2603), brackish water fish (301) and aquatic environments (115) and identified V. parahaemolyticus in 29 (1.1%), 171 (56.8%) and 43 (37.4%) samples, respectively. Incidence of pathogenic V. parahaemolyticus with virulence encoding thermostable-direct haemolysin gene ( tdh ) was detected mostly in fishes (19.3%) and waters (15.6%) than clinical samples (1.04%). The pandemic strain marker genes ( toxRS and PGS-sequences) have been detected relatively more in water (6%) and fish (5%) samples than in clinical samples (0.7%). Majority of the V. parahaemolyticus isolates from clinical cases and fish samples (26.3%) belonged to classical pandemic serovars (O3:K6). In addition, several newly recognised pandemic serovars have also been identified. Pulsed field-gel electrophoresis (PFGE) analysis showed clonal relatedness (60–85%) of V. parahaemolyticus from different sources. The study observation revealed that the brackish water fishes and water bodies may act as a reservoir of pathogenic V. parahaemolyticus . Emergence of several new serovars of pandemic V. parahaemolyticus signifies the changing phenotypic characteristics of the pathogen.